Application of Public Sector Accounting in The Financial System of The Tongke-Tongke Village Government - Riny Jefri; Nurul Maghfirah Surianto; Muhammad Rafly Awaluddin (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to analyze the application of public sector accounting in the financial system of the Tongke-Tongke Village Government, particularly in the preparation and reporting of the Village Budget (APBDes). The method used is a qualitative descriptive approach with a focus on an in-depth understanding of the accounting process, financial management, and compliance with applicable regulations. The results showed that the Tongke-Tongke Village Government has appropriately applied public sector accounting principles in accordance with the provisions of Permendagri Number 113 of 2014 and Government Accounting Standards (SAP). The utilization of the village financial information system (Siskeudes) supports regularity of reporting and promotes transparency and accountability in village financial management. The village also complied with budget allocation requirements, with 30% for apparatus expenditure and 70% for development and community empowerment. These findings reflect the village government's strong commitment to good governance and improving community welfare.